Journey to Quality 6.0: Evolution of quality management across industrial revolutions - Smajdorova, Tereza (Trends in Computer Science and Information Technology, 2024)
This article explores the development of industrial revolutions and their relationship to the evolution of quality management from the first to the fifth revolution. The analysis covers significant changes in manufacturing processes, technologies, and business models that shaped the concept of quality in industry. Special emphasis is placed on the transition from manual labor to automation, the development of industrial standards, and the increasing role of quality in corporate leadership. Furthermore, the article introduces considerations about the potential form of the sixth industrial revolution, highlighting the impacts of artificial intelligence, the Internet of Things, and digitization on the future of industry. A focal point of interest is the visualization of “Quality 6.0,” representing the next level of quality management in light of emerging technologies and industrial trends. This article offers a perspective on how quality management could respond to the anticipated sixth industrial revolution and what innovative quality might look like in the digital era.